2020
DOI: 10.1002/iub.2274
|View full text |Cite
|
Sign up to set email alerts
|

Lack of miR‐1246 in small extracellular vesicle blunts tumorigenesis of laryngeal carcinoma cells by regulating Cyclin G2

Abstract: Small extracellular vesicle (sEV) has precise impacts on tumor microenvironment and play vital functions in intercellular interaction. However, the functional role of sEV miRNA on laryngeal squamous cell carcinoma (LSCC) is largely unresolved. Here, the expression of miR‐1246 in LSCC tissues and plasma sEV was examined. The internalization ability of sEV was determined by uptake assay. Then, the source and purity of sEV were checked through RNase and/or pharmacological inhibitors application. The invasion, mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 33 publications
3
12
0
Order By: Relevance
“…Overexpression of miR-1246 promoted UVB-induced apoptosis in HaCaT cells [38]. Previous results indicated that lack of miR-1246 arrested the cell cycle at the G0/G1 phase [32]. Similar to that, our cell cycle distribution assay proved that loss of miR-1246 could halt cells at the G0/G1 phase in chemo-resistant leukemia cells (Figure 2E).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Overexpression of miR-1246 promoted UVB-induced apoptosis in HaCaT cells [38]. Previous results indicated that lack of miR-1246 arrested the cell cycle at the G0/G1 phase [32]. Similar to that, our cell cycle distribution assay proved that loss of miR-1246 could halt cells at the G0/G1 phase in chemo-resistant leukemia cells (Figure 2E).…”
Section: Discussionsupporting
confidence: 86%
“…After Annexin V-FITC and PI staining, the data checked by flow cytometry showed that loss of miR-1246 promoted cell apoptosis, and this was statistically significant (Figure 2D). Similar to previous cell cycle results at the small extracellular vesicle level [32], lack of miR-1246 in chemo-resistant leukemia cells repressed the advancement of cell cycle by halting cells at the G0/G1 phase. While ADM treatment led to cell cycle arrest and the accumulation of cells at the G2/M phase (Figure 2E).…”
Section: Inhibition Of Mir-1246 Increased Chemo-sensitivity Of Drug-resistant Leukemia Cellssupporting
confidence: 86%
“…Although most of the evidence in the literature supports a role for CCNG2 in limiting G1/S phase transition [ 23 , 24 ], there are indications that CCNG2 could participate in G2/M regulation [ 23 , 25 , 26 ]. We previously proved that CCNG2 siRNA application in LSCC cell lines contributes to the increased G2/M phase proportion [ 16 ]. This is consistent with our findings that the overexpression of CCNG2 in FaDu cells led to a decrease in the G2/M phase proportion.…”
Section: Discussionmentioning
confidence: 99%
“…#HPA034684, 1:1000) in 5% BSA were used. Refer to our previous articles for the rest of the steps [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Lack of miR-1246 in these vesicles abolished development of this kind of cancer. miR-1246 content of small vesicles could participate in the pathoetiology of laryngeal squamous cell carcinoma through suppressing CCNG2 expression ( Huang Q. et al, 2020 ). miR-1246 is involved in the progression of melanoma via changing expression levels FOXA2 ( Yu et al, 2020 ).…”
Section: Cell Line Studiesmentioning
confidence: 99%